Implementation of Grant Proposal Policy Through Electronic Grant System in DKI Jakarta Province - Ahmadi, Juwanda Surya; Sampurna, Firman Agung (Jurnal Ilmiah Ilmu Administrasi Publik, 2024)
This study examines the implementation of grant proposal policies through electronic grant systems in DKI Jakarta Province. The purpose of this study is to determine the implementation of grant proposal policies through electronic grant systems in DKI Jakarta Province and to examine the factors that influence it based on communication variables, resources, dispositions and institutional structures. The research method used is a qualitative method with a post-positivism approach, the research model is descriptive. Data collection through observation, interviews and documentation. Data analysis techniques are carried out by data reduction, data presentation, data verification and drawing conclusions. Data validity is carried out using triangulation techniques. The results of the study indicate that the implementation of the grant proposal policy through the electronic grant system in DKI Jakarta Province has been running quite well, but consistency between regulations is still lacking, the quantity of policy implementing staff is still lacking. Technical instructions (juknis) for implementing the policy specifically have not been made, and the SOP still uses the old SOP. Communication factors , resources, disposition and institutional structure influence the implementation of this grant proposal policy and each of these variables influence each other